2022
DOI: 10.1002/ehf2.14008
|View full text |Cite
|
Sign up to set email alerts
|

Elderly aortic stenosis patients' perspectives on treatment goals in transcatheter aortic valvular replacement

Abstract: Aims Transcatheter aortic valvular replacement (TAVR) is increasingly being performed for elderly patients with aortic stenosis (AS), and current guidelines acknowledge the importance of shared decision-making in their management. This study aimed to evaluate elderly symptomatic severe AS patients' perspectives on their treatment goals and identify factors that influence their treatment choice. Methods and ResultsWe performed a pre-procedural cross-sectional survey using a questionnaire at a single university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A second most widely applied SDM step was the exploration of patient wishes and concerns in the decision-making process (step 4)[ 27 , 29 , 32 34 , 36 , 37 ]. Description of how the decision was made was described by six studies [ 29 , 34 , 36 , 38 , 39 , 41 ]. Four studies reported about patient’s goals of care regarding immediate care outcomes which can be attributed to the second step of SDM – the key message [ 30 , 35 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A second most widely applied SDM step was the exploration of patient wishes and concerns in the decision-making process (step 4)[ 27 , 29 , 32 34 , 36 , 37 ]. Description of how the decision was made was described by six studies [ 29 , 34 , 36 , 38 , 39 , 41 ]. Four studies reported about patient’s goals of care regarding immediate care outcomes which can be attributed to the second step of SDM – the key message [ 30 , 35 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Description of how the decision was made was described by six studies [ 29 , 34 , 36 , 38 , 39 , 41 ]. Four studies reported about patient’s goals of care regarding immediate care outcomes which can be attributed to the second step of SDM – the key message [ 30 , 35 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its prevention therefore represents a priority objective across all levels of healthcare in many geographies. From a patient's perspective, stroke represents the most feared complication of TAVR 8,9 . Contemporary stroke rates related to TAVR remain at 2-4% 3,10,11 , with no significant reduction in recent times 3,4 .…”
Section: Introductionmentioning
confidence: 99%